Antibacterial Activity Test of Combination of Chitosan and Ethanol Extract of Cocoa Leaves (Theobroma Cacao L.) Against Salmonella Typhi Bacteria - Saifullah Al Fahmi; Luluk Aniqoh Meliana Putri; Ivan Junius Mesak; Juvita Herdianty (Strada Journal of Pharmacy, 2024)
Introduction:Typhoid fever is a systemic infectious disease caused by the bacterium Salmonella typhi. The increasing antibiotic resistance of Salmonella typhi has spurred interest in natural antibacterial agents. This study examines the antibacterial activity of a combination of chitosan and ethanol extract of cocoa leaves (Theobroma cacao L.) against Salmonella typhi. Methods: The research involved extracting cocoa leaves using ethanol and combining the extract with chitosan. The antibacterial activity was evaluated using the well diffusion method on Salmonella typhi. The combination of chitosan and cocoa leaf extract was tested at various concentrations, and chloramphenicol was used as a positive control. Results: The combination of chitosan and cocoa leaf extract showed significant antibacterial activity, with the best results obtained at higher concentrations. The zone of inhibition for the combination at 600 ppm was comparable to that of the positive control of chloramphenicol. Conclusion: The study suggests that the combination of chitosan and cocoa leaf extract has the potential to be developed as an alternative treatment for typhoid fever, particularly against antibiotic-resistant strains of Salmonella typhi.